The Effect of Liveworksheets-Based E-LKPD on High School Students’ Interests and Learning Outcomes in Magnetic Induction Material - Shofira Amatullah; Alex Harijanto; Subiki Subiki (Universitas Lambung Mangkurat, 2025)
The liveworksheets-based E-LKPD implemented in SMA Negeri 3 Lumajang aims to assess whether there is an influence on the interest and learning outcomes of high school students on the subject of magnetic induction. The type and design of this research is true-experimental and Posttest-Only Control Design. The samples used were class XII-1 as the experimental class and XII-2 as the control class which were determined using purposive sampling area technique. After the application of e-LKPD based on liveworksheets, there were differences between the two sample groups on student interest and learning outcomes after hypothesis testing. The results show the value of Sig. (2-tailed) value of 0.035 on learning interest and Sig. (2-tailed) is 0.047 on learning outcomes. It can be said that the liveworkheets-based e-LKPD has an effect on student interest in learning as shown by student focus, student activeness, and student involvement during learning and supported by student interviews after the study. The effect on student learning outcomes is due to differences in the treatment given and is shown by the results of posttests obtained by students.